2019
DOI: 10.3390/polym11091398
|View full text |Cite
|
Sign up to set email alerts
|

Pore Structure and Properties of PEEK Hollow Fiber Membranes: Influence of the Phase Structure Evolution of PEEK/PEI Composite

Abstract: Poly(ether ether ketone) (PEEK) hollow fiber membranes were successfully prepared from miscible blends of PEEK and polyetherimide (PEI) via thermally-induced phase separation (TIPS) with subsequent extraction of the PEI diluent. The phase structure evolution, extraction kinetics, membrane morphology, pore size distribution and permeability for the hollow fiber membrane were studied in detail. Extraction experiments, differential scanning calorimetry (DSC) and dynamic mechanical thermal analysis (DMA) studies s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Blends of PEEK/PEI have been studied due to their high miscibility, which can offer a chance to balance their properties, minimizing their respective drawbacks [1,2,[5][6][7][8][9][10][11][12][13]. Applications in membranes and welding processes [14][15][16], as well as in the aerospace industry, where good mechanical properties at high temperatures are required [17], has increased the interest in PEEK/PEI blends. Several studies have demonstrated the high miscibility of both polymers in all blend compositions due to the identification of a single glass transition [2,5,10,12,17], which varied nearly as predicted by the Fox equation [5,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Blends of PEEK/PEI have been studied due to their high miscibility, which can offer a chance to balance their properties, minimizing their respective drawbacks [1,2,[5][6][7][8][9][10][11][12][13]. Applications in membranes and welding processes [14][15][16], as well as in the aerospace industry, where good mechanical properties at high temperatures are required [17], has increased the interest in PEEK/PEI blends. Several studies have demonstrated the high miscibility of both polymers in all blend compositions due to the identification of a single glass transition [2,5,10,12,17], which varied nearly as predicted by the Fox equation [5,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Then precursor fibers were annealed at 270 °C for 3 h and were immersed in extractants (80 vol% N ‐methylpyrrolidone, 10 vol% ethanolamine and 10 vol% water) for 1 h to remove PEI and obtain PEEK hollow fiber membrane. The specific preparation method of PEEK hollow fiber membrane has been demonstrated in detail in our previous work 16 …”
Section: Methodsmentioning
confidence: 99%
“…Poly(ether ether ketone) (PEEK) is a kind of semicrystalline aromatic engineering thermoplastic polymer with outstanding thermal resistance, chemical stability and comprehensive mechanical properties 14,15 . The continuous service temperature of PEEK is up to about 250 °C and it is almost insoluble in any common solvent at room temperature 16 . Therefore, PEEK is considered as a potential high performance membrane material which can be used in high‐temperature resistant ultrafiltration and microfiltration processes, 14 fuel cells 17–19 and gas separation 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the comparative advantages of each thermoplastic (e.g., the thermal stability of PEI and the chemical resistance of PEEK), it is of great interest to combine their properties and minimize their respective drawbacks by means of a PEEK/PEI blend, whose molecular miscibility is a proven fact [ 13 , 14 , 15 , 16 ]. Until now, the melt blending process, which commonly uses a twin-screw extruder, has been the most widely used technique in manufacturing PEEK/PEI polymer blends [ 17 , 18 , 19 , 20 , 21 , 22 ]. Although full PEEK/PEI interpenetration has been shown to provide good thermal and mechanical properties, there are significant disadvantages in terms of the physical and chemical properties of these materials when both are found in a homogeneous mixture.…”
Section: Introductionmentioning
confidence: 99%